Diretrizes para a gestão da conversão do conhecimento tecnológico em patentes - Lichti, Paulo Aneas (2013)
This work was carried out with the intention of developing a set of guidelines that seeks to promote the conversion of technological knowledge into effective appropriation of intellectual capital as an intangible asset, through the production of patents. Based on the theoretical references for knowledge management activities, on project office management activities and on the process known as "innovation funnel", and on the method of research-action, the guidelines were developed. Once implemented in a private held business environment that invests in research and development as part of its strategy, it was observed a significant increase in the conversion capacity of technological knowledge generated in patent applications in the order of 16 times over a period prior to the use of those guidelines. Thus, it is concluded that the proposed model is effective and meaningful to provide better conditions for increasing intangible assets of the organization that it was the subject of the study, mainly due to the application of the resources of knowledge management.